PERNERAPAN ERGONOMI DI INDUSTRI KELAPA SAWIT MENGGUNAKAN METODE OVAKO WORKING ANALYSIS SYSTEM PADA STASIUN PERNYORTIRAN TBS (STUDI KASUS DI PT XYY) - Aris Fiatno; Nur Aliza (Research Center University of Pahlawan Tuanku Tambusai, 2020)
Harvesting, loading and sorting activities in palm oil industry that conducted manually have some risks that can cause musculoskeletal disorders (MSDs). This is happened due to repetitive of manual working, standing and bending position for 8 hours and 6 working days, this activity does not match the anthropometry of worker body. The analysis of the Nordic Body MAP questionnaire shows that the biggest complaints experienced by harvest workers are on the back (90%), right shoulder (60%), waist (15%), right calf (40%) the same as the forearm and left calf (30%). ).Work posture analysis using the OWAS method also supports the results of the NBM questionnaire analysis with the results of the analysis of the dominant bent shoulder attitude carried out by 68% (category 2), the attitude of the two arms is 53% (category 2) and the stance of the legs resting on both bent knees. 47% (category 3) with a combination of harvest posture code 4-2-2-2 (category 3).